2023
DOI: 10.3390/ijms24087626
|View full text |Cite
|
Sign up to set email alerts
|

Mutated Flt3Lg Provides Reduced Flt3 Recycling Compared to Wild-Type Flt3Lg and Retains the Specificity of Flt3Lg-Based CAR T-Cell Targeting in AML Models

Abstract: The cells of acute myeloid leukemia are defined by clonal growth and heterogenous immunophenotypes. Chimeric antigen receptors (CARs) commonly recognize molecular targets by single-chain antibody fragments (scFvs) specific to a tumor-associated antigen. However, ScFvs may form aggregates, thus stimulating tonic CAR T-cell activation and reducing CAR T-cell functioning in vivo. Harnessing natural ligands as recognition parts of CARs, specific targeting of membrane receptors can be achieved. Previously, we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, recent studies have also found that ETFDH plays an important role in the development of several diseases [ 55 , 56 ], suggesting the need for future research in order to explore its association with biological pathways that drive PTSD.Fms-related receptor tyrosine kinase 3 ligand (FLT3LG) is a growth factor that binds to and forms non-covalent dimers with FLT3 (CD135), acting as an agonist [ 57 ]. FLT3LG stimulates the differentiation and proliferation of dendritic cells [ 58 ] and has a potential therapeutic value in treating autoimmune diseases and tumors [ 57 , 59 ]. However, there is relatively limited research on FLT3LG, and further exploration is needed regarding its expression levels, functions, and clinical value in various diseases [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have also found that ETFDH plays an important role in the development of several diseases [ 55 , 56 ], suggesting the need for future research in order to explore its association with biological pathways that drive PTSD.Fms-related receptor tyrosine kinase 3 ligand (FLT3LG) is a growth factor that binds to and forms non-covalent dimers with FLT3 (CD135), acting as an agonist [ 57 ]. FLT3LG stimulates the differentiation and proliferation of dendritic cells [ 58 ] and has a potential therapeutic value in treating autoimmune diseases and tumors [ 57 , 59 ]. However, there is relatively limited research on FLT3LG, and further exploration is needed regarding its expression levels, functions, and clinical value in various diseases [ 60 ].…”
Section: Discussionmentioning
confidence: 99%